EFFECT OF PRENATAL EXPOSURE TO KETAMINE ON NEWBORN RAT FRONTAL CORTEX: IMMUNOHISTOCHEMICAL STUDY WITH TUNEL TEST (Iraqi Journal of Medical Sciences, 2016)
Background:Ketamine as an analgesic drug is widely used to provide sedation for minor procedures. It was reported that the use of this drug causes deletion of large numbers of neurons from the developing brain.Objectives:To investigate the effect of prenatal ketamine exposure on the newborn rat frontal cortex using immunohistochemical TUNEL test.Methods:Seventy two pregnant rats were divided into three groups: I, II, and III (24 rat for each group), and exposed to ketamine at the 7th day, 11th day, and 18th day, of gestational age. Each group was subdivided into control subgroup A injected intraperitoneally with normal saline, and the subgroups B, C and D injected with intraperitoneal ketamine with 5 mg/kg, 10 mg/kg, and 20 mg/kg, respectively. Paraffin block sections of newborn rat frontal cortices were investigated by TUNEL test. Results:Counting of fluorescent cells showed progressive increase in mean values with increased dose of ketamine injection and advancing age of prenatal exposure to ketamine. Significant variability was demonstrated between the control subgroup A and the other subgroups, and between the subgroups of each group, whereas, non-significant variability was observed between the counted mean differences values obtained for subgroup B in all groups (I, II, and III) compared to that of the control subgroup A.Conclusion:Prenatal exposure to ketamine in a dose of 5mg/kg was a relatively non-toxic in all studied groups compared to the control subgroup. Apoptosis in frontal cortical tissue was involved in the mechanism of neuronal death caused by ketamine exposure during pregnancy.Keywords:Frontal, cortex, prenatal, ketamine, neurotoxicity, immnuohistochemistry.
Keywords: Frontal; cortex; prenatal; ketamine; neurotoxicity; immnuohistochemistry